The Effect of Albert Bandura Social Cognitive Conservation using Sociodrama Techniques to Improve Students of Impact and Empathy with Setting Lesson Study of Class X Aph C In SMK Negeri 1 Singaraja - Chika Paramitha; Ketut Dharsana (RedwhitePress)
This study aims to determine the application of Albert's bandura social cognitive counseling with sociodrama techniques to increase sympathy and student x empathy. type of quasi-experimental research with pre-test and post-test control group design. a sample of 32 students with 31 df . the method of collecting data using a sympathy questionnaire and empathy, 30 items. The results of data analysis, the value of tcount is 2.1866 and ttable is 1.667 with (2.1866 > 1.667) so ho is rejected, and ha is accepted. So there is a significant difference. It was concluded that cognitive awareness of social bandura albert with sociodrama techniques was effective to increase student sympathy and empathy.